2013
DOI: 10.1093/ije/dyt042
|View full text |Cite
|
Sign up to set email alerts
|

Tubal ligation and risk of ovarian cancer subtypes: a pooled analysis of case-control studies

Abstract: We found that the protective effects of tubal ligation on ovarian cancer risk were subtype-specific. These findings provide insights into distinct aetiologies of ovarian cancer subtypes and mechanisms underlying the protective effects of tubal ligation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(134 citation statements)
references
References 42 publications
12
118
0
4
Order By: Relevance
“…The Australian Ovarian Cancer Study group reported strikingly similar patterns of risk for serous ovarian and fallopian tube cancers and different results for primary peritoneal cancers suggesting that the former may be linked . Additional studies have reported that the protective effect of tubal ligation is subtype specific with risk reduction for invasive endometrioid and clear cell cancers (Sieh et al 2013b). Studies on women with BRCA1/BRCA2 mutations have provided convincing evidence that highgrade serous cancers can arise from cells within the fallopian tube (reviewed in Berns & Bowtell (2012)).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…The Australian Ovarian Cancer Study group reported strikingly similar patterns of risk for serous ovarian and fallopian tube cancers and different results for primary peritoneal cancers suggesting that the former may be linked . Additional studies have reported that the protective effect of tubal ligation is subtype specific with risk reduction for invasive endometrioid and clear cell cancers (Sieh et al 2013b). Studies on women with BRCA1/BRCA2 mutations have provided convincing evidence that highgrade serous cancers can arise from cells within the fallopian tube (reviewed in Berns & Bowtell (2012)).…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Female occlusive sterilization procedures are estimated to reduce a woman's lifetime risk of ovarian cancer by 24-34% [6,7]. However, a recent meta-analysis Contraception 95 (2017) 505 -508 demonstrated that women who had undergone salpingectomy had an overall 49% reduction in ovarian carcinoma risk [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in ovarian cancer risk has been reported by others (Cibula et al, 2011;Rice et al, 2012;Sieh et al, 2013). We previously reported significant heterogeneity by histological type of ovarian cancer, finding that tubal ligation was associated with a modest reduction of serous tumours overall (RR ¼ 0.84, 95% CI: 0.77-0.92), and about a 20% reduction in risk of high-grade serous carcinoma, and almost a halving of risk of endometrioid and clear cell ovarian tumours (Gaitskell et al, 2016).…”
Section: Discussionmentioning
confidence: 54%